PRODUCTIVITY OF WORD BUILDING MEANS, MAJOR AND MINOR TYPES OF WORD FORMATION (Modern education and development, 2025)
The article investigates the productivity of both major and minor word-formation processes in the English language. It analyzes the most active mechanisms—such as affixation, compounding, conversion, clipping, and blending—that play a vital role in expanding the vocabulary. Additionally, it covers less productive or marginal processes like back-formation, acronyms, reduplication, coinage, and borrowing. The study emphasizes the dynamic character of word-building and how it reflects social, cultural, and technological changes in contemporary English.